The presence of ampicillin-resistant coliforms in urban floodwaters of a coastal city in the southeastern United States - Squiggins, Kayla T.; Fullerton, Heather; Vulava, Vijay M. (Frontiers in Water, 2024)
Rapid urbanization in coastal areas worldwide, combined with intense precipitation events and coastal flooding exacerbated by climate change, poses an existential challenge for many coastal communities. Floodwater in coastal urban areas contains nonpoint source pollutants, such as trace metals and fecal coliforms, but the presence of fecal coliforms resistant to antibiotics poses an additional threat to human health and has yet to be reported. In this study, floodwater samples were collected from four locations in Charleston, SC, a medium-sized coastal city in the southeastern United States. All sites were impacted by flooding: two by tidal and rainfall flooding, one by tidal flooding, and one by stormwater runoff. Since ampicillin is a commonlyprescribed antibiotic for both humans and animals, this study aimed to analyze the patterns of ampicillin-resistant coliform (AmpRC) concentrations as correlated to flood-source and land-use patterns. Floodwater from all areas contained AmpRC and trace metals, with varying contaminant concentrations based on the flood source. No correlations were observed between coliform and trace metal concentrations. Analysis of land-use patterns demonstrated a positive correlation between percent coverage of impervious surfaces and coliform concentrations at all the sites. Overall, the results suggest that land-use patterns increase the prevalence of antibioticresistant coliforms and increase the likelihood of human exposure to these potential pathogens. Climate change is expected to exacerbate the presence of antibiotic-resistant bacteria in floodwater generated from rainfall and tidal flooding in coastal cities. Cities like Charleston, SC are experiencing rapid urbanization and increased coastal flooding, making this research particularly relevant.